2014
DOI: 10.1155/2014/732731
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Organizational Factors Associated with Elbow/Forearm and Hand/Wrist Disorder among Sewing Machine Operators of Garment Industry in Ethiopia

Abstract: Occupational health problems related to upper limp musculoskeletal disorders were the major issue among sewing machine operators of garment industries in Ethiopia. The aim of this study was to assess the prevalence and associated risk factors of work related elbow and wrist musculoskeletal disorders among sewing machine operators of garment industries in Galan City, Oromia Regional State. A cross-sectional study was conducted from April 1 to 30, 2012. A total of 422 study subjects were included in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 10 publications
(13 reference statements)
0
25
0
2
Order By: Relevance
“…9 The cause of long term disability and sick leave of WMSDs among tailors retirement fund in the world. 10 The main risk factor for the development of the MS disorder for long time adopting sedentary working style with wrong posture. In WMSDs, the most common signs and symptoms are muscle tightness, joint stiffness, swelling, numbness, redness, skin color changes and decreased sweating of the hands.…”
Section: Introductionmentioning
confidence: 99%
“…9 The cause of long term disability and sick leave of WMSDs among tailors retirement fund in the world. 10 The main risk factor for the development of the MS disorder for long time adopting sedentary working style with wrong posture. In WMSDs, the most common signs and symptoms are muscle tightness, joint stiffness, swelling, numbness, redness, skin color changes and decreased sweating of the hands.…”
Section: Introductionmentioning
confidence: 99%
“…Characteristics Of Original Articles In this study to estimate the pooled magnitude of work related injury a total of 8025 workers from MSWM, construction and textile industry were involved. Concerning geographical distribution of the studies, the 17 studies were obtained from the four regions of the country: six studies from Addis Ababa (10,19,(21)(22)(23)30), three from Oromia (24,27,29), seven (7) from Amhara (11,17,18,20,25,26,28), and one from Southern Nations, Nationalities and Peoples' Region (SNNPR) (29). The highest prevalence of occupational injury and illness (84.7%) was reported in Addis Ababa (10) whereas the lowest prevalence (31.4%) was reported from a study done in Arba Minch (SNNPR) (9).…”
Section: Search Resultsmentioning
confidence: 99%
“…Lastly the pooled odds of work related injury among those workers using PPE was 52% less than those who did not use PPE at work place (0.48 (95%CI: 0.36, 0.65)). To calculate the pooled odds ratio of alcohol drinking habit (9,11,17,18,26,28,30,31), cigarette smoking habit (18,24,26,30,31), khat chewing habit (9, 22, 26-28, 30, 31), work related stress (9,20,26,29,30), level of education (9,11,18,24,26,30,31), and use of PPE (9,11,18,19,22,26,27,(29)(30)(31) reports of a minimum of 5 to 10 studies were included.…”
Section: Subgroup Analysismentioning
confidence: 99%
“…However, musculoskeletal disorders remain a major global health concern and an immense burden for LMICs like Ethiopia where health budgets are already constrained and channeled life-threatening conditions. Studies have shown that musculoskeletal pain prevalence among the working population in Ethiopia varies from 35% to 74.5% [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%